POLA DAN DETERMINAN PENAWARAN TENAGA KERJA PEREMPUAN DI PROVINSI SULAWESI TENGAH TAHUN 2011 (ANALISIS DATA SUSENAS 2011) - , Indyah Kusumaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the patterns of female labor supply represented by the female labor force participation in economic,social and demographics factors in Central Sulawesi. This study are expected to be known : (1) An overview of how the pattern of the female labor supply by wages, school enrollment, marital status, status in the household, per capita per month expenditure of households and urban-rural housing in Central Sulawesi